From star clusters to field populations: survived, destroyed and migrated clusters - AAVV (Il Colle di Galileo, 2024)
Cluster formation: star formation models, spatial and temporal variation of the rate of cluster formation Cluster demographics: the Gaia mission, new identification techniques based on artificial intelligence, description of new samples, complete characterisation of existing samples; presence of halo and tidal tails in clusters. Cluster disruption and stellar migration: cluster disruption models, role of stellar migration in the redistribution of populations, chemical and kinematic evidence of radial and vertical displacement, differences between field stars and clusters, numerical models of cluster migration and disruption rates. Clusters in current and next generation instruments/surveys: what are the key open questions that we could tackle with the next generation of instruments and surveys, e.g., WEAVE@WHT, 4MOST@VISTA, MOONS@VLT.